Enzymatic changes in granulosa cells of developing goat follicles - SANGHA, G K; MARWAHA, A (The Indian Journal of Animal Reproduction, 2023)
Enzyme activities were measured in granulosa cells from small (<2mm), medium (2-5mm) and large sized (>5mm) follicles of goat ovaries. Acid and alkaline phosphatases and lactate dehydrogenase increased in the granulosa cells from small to large follicles. Levels of enzyme 3 HSDH was very low in small and medium sized follicles and it increased dramatically in the granulosa cells oflarge follicles. The changes in enzyme systems have been correlated with the metabolism and the steroid biosynthesis in the granulosa cells of the maturing follicles.